Dinamika Psikologis Perkawinan Poligami (Menyingkap Suasana Batin Isteri Yang Dipoligami) - Suaidi Suaidi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Marriage is a bond between two men and women to form a happy and eternal household. The formation of a household is symbolic, that humans have a goal to develop life, this symbol can be realized when both parties bind themselves to move together under any circumstances. Marriage, which is symbolized as a bond and agreement, legally can be reviewed when the main goal is not fulfilled due to inconsistencies between the two parties deviating from the original purpose of forming a family. The review of the marriage agreement may end with a legal process or due to natural causes such as the death of one of them. Marriage, which was originally intended to form a happy and eternal household, could be broken up because the husband and wife are not committed to living life together. The principle of marriage, both according to Islamic Shari'at and Law Number 1 of 1974 concerning marriage contains the principle of monogamy, namely a man may only be paired with a woman and vice versa, but under certain conditions, Islamic Shari'at and the Law The law provides space and opportunities for a man to have more than one wife, namely polygamy. In practice, polygamous marriages still have pros and cons. There are pros and cons of opinion on polygamous marriages due to irregularities in its implementation. These deviations will be the object of research.